Structural insight into [Fe-S-2-Mo] motif in electrochemical reduction of N-2 over Fe-1-supported molecular MoS2 - Zheng, J; Wu, S; Lu, L; Huang, C; Ho, P-L; Kirkland, A; Sudmeier, T; Arrigo, R; Gianolio, D; Tsang, SCE (Royal Society of Chemistry, 2020)
The catalytic synthesis of NH3 from the thermodynamically challenging N2 reduction reaction under mild conditions is currently a significant problem for scientists. Accordingly, herein, we report the development of a nitrogenase-inspired inorganic-based chalcogenide system for the efficient electrochemical conversion of N2 to NH3, which is comprised of the basic structure of [Fe–S2–Mo]. This material showed high activity of 8.7 mgNH3 mgFe−1 h−1 (24 μgNH3 cm−2 h−1) with an excellent faradaic efficiency of 27% for the conversion of N2 to NH3 in aqueous medium. It was demonstrated that the Fe1 single atom on [Fe–S2–Mo] under the optimal negative potential favors the reduction of N2 to NH3 over the competitive proton reduction to H2. Operando X-ray absorption and simulations combined with theoretical DFT calculations provided the first and important insights on the particular electron-mediating and catalytic roles of the [Fe–S2–Mo] motifs and Fe1, respectively, on this two-dimensional (2D) molecular layer slab.